ACM Internet Measurement Conference (IMC) Distinguished Paper - Sirivianos, Michael (My University, 2026)
2018: ACM Internet Measurement Conference (IMC) - Distinguished Paper “On the Origins of Memes by Means of Fringe Web Communities”
Keywords: Sciences